2011
DOI: 10.1002/chem.201101024
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Chemical Microenvironment and Redox Environment on Thiol–Disulfide Exchange Kinetics

Abstract: The interplay between the chemical microenvironment surrounding disulfides and the redox environment of the media on thiol-disulfide exchange kinetics was examined by using a peptide platform. Exchange kinetics of up to 34 cysteine-containing peptides were measured in several redox buffers. The electrostatic attraction/repulsion between charged peptides and reducing agents such as glutathione was found to have a very pronounced effect on thiol-disulfide exchange kinetics (differences of ca. three orders of mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 21 publications
(13 reference statements)
3
74
0
Order By: Relevance
“…We found that the first-order rate of glutathionylation at Cys63 was nearly 5 times higher than the glutathionylation at Cys47 (Figure 4C, 5A). The lower reactivity of Cys47 is likely caused by the presence of negatively charged neighboring residues (Figure 5B) (Wu et al, 2011). Refolding measurements of I91-Cys63 in the presence of 10 mM GSSG confirmed that the glutathionylation rate changes linearly with the concentration of GSSG, as expected for a first-order chemical reaction (Figures 5C, S4).…”
Section: Resultsmentioning
confidence: 99%
“…We found that the first-order rate of glutathionylation at Cys63 was nearly 5 times higher than the glutathionylation at Cys47 (Figure 4C, 5A). The lower reactivity of Cys47 is likely caused by the presence of negatively charged neighboring residues (Figure 5B) (Wu et al, 2011). Refolding measurements of I91-Cys63 in the presence of 10 mM GSSG confirmed that the glutathionylation rate changes linearly with the concentration of GSSG, as expected for a first-order chemical reaction (Figures 5C, S4).…”
Section: Resultsmentioning
confidence: 99%
“…The amino-acid sequence of peptides was shown to have a profound effect on the rate of thiol-disulfide exchange reactions with particular influence of ionic amino acids in close proximity to the thiolate (111). In proteins, due to their tertiary and quaternary structures, charged amino acids that are sequentially well separated can also come close to the reaction center and affect reactivity.…”
Section: Charges Coulombic and H-bonding Interactions With Neighborimentioning
confidence: 98%
“…Not only the biological surrounding influences the fate of disulfide bonds, but also the molecular chemical environment of disulfide bonds within a dynamic carrier can be tuned. For example, by stabilizing disulfide bonds by bulky groups providing sterical hindrance (47,110), different exposure (core or surface) within a nanoparticle system (as illustrated in the PAMAM polymer example discussed earlier), the electrostatic environment facilitating or restricting electrostatic interaction with a reducing agent (5,125), or the number and positioning of multiple disulfide bonds (126).…”
Section: Klein and Wagnermentioning
confidence: 99%